Analysis of the Importance of Islamic Religious Education and Life Skills in Forming a Noble Young Generation in Indonesia - Amaludin Bahansubu; Muhammadong Muhammadong; Mursyidi Abdul Jalil; Sabil Mokodenseho (Jurnal Pendidikan West Science, 2023)
This study investigated the interconnected roles of Islamic religious education and life skills in shaping the character development of young people in Indonesia. A sample of 200 participants from various demographics provided insights through a survey. Descriptive statistics showed positive perceptions towards Islamic religious education, life skills, and character development. Correlation analysis showed a significant positive relationship between these variables, and multiple regression analysis strengthened their combined influence. The findings emphasize the importance of integrating religious teachings and practical skills in the education curriculum, with consideration of the culture that influences character development. This research contributes to the broader discourse on education, providing valuable insights for policy makers and educators in encouraging holistic development among Indonesian youth.